In-situ SIMS uraninite U–Pb dating and genesis of the Xianshi granite-hosted uranium deposit, South China - Luo, Jin-Cheng; Hu, Rui-Zhong; Fayek, Mostafa; Li, Chu-Si; Bi, Xian-Wu; Abdu, Yassir; Chen, You-Wei (Ore geology reviews, 2015)
The southeastern part of the Nanling metallogenic province, China is host to numerous granite-hosted vein-type hydrothermal uranium deposits. The geology and geochemistry of these deposits have been extensively studied. However, accurate and precise ages for the uranium mineralization are scarce because the uranium minerals in these deposits are usually fine grained, and may have formed in several stages. Therefore, the ages previously obtained by the bulk dating techniques are possibly a mixed age. The Xianshi uranium deposit, located in the southeastern part of the Guidong granite complex, is a major uranium deposit in South China. The uranium mineralization from this deposit is mainly fine grained uraninite in quartz or calcite veins which are spatially associated with the Cretaceous mantle-derived mafic dykes. Micro-Raman spectroscopy and X-ray diffraction analyses indicate that the dominant uranium mineral occurs as a rare form of uraninite (U3O7). Three distinct generations of uranium minerals have been identified based on petrographic and field relations. Stage 1 uraninite has the lowest UO2 and highest PbO contents whereas Stage 3 uraninite has the highest UO2 and lowest PbO contents. Uraninite from the Xianshi deposit was dated using an in-situ SIMS U–Pb dating technique. The results show three distinct age groups: 135±4Ma, 113±2Ma and 104±2Ma, which are in excellent agreement with the ages of three episodes of mantle-derived mafic dykes. Therefore, the Xianshi uranium deposit has experienced at least three hydrothermal events that are responsible for the deposition of uranium ores, which are genetically related to the emplacement of three sets of mafic dykes. •Uranium in the Xianshi uranium deposit occurs as a rare form of uraninite (U3O7).•Three diverse generations of uranium minerals have been identified.•SIMS uraninite U-Pb dating shows three age groups of 135±4,113±2 and 104±2Ma.•These ages are in agreement with those of three episodic mafic dykes in the region.